Antifouling effect of bioactive compounds from marine sponge Acanthella elongata and different species of bacterial film on larval attachment of Balanus amphitrite (cirripedia, crustacea) - Ganapiriya,Viswambaran (2012)
The antifouling activity of bioactive compounds from marine sponge Acanthella elongata (Dendy) and five species of bacterial biofilm were studied. Larvae of Balanus amphitrite (Cyprids and nauplii) were used to monitor the settlement inhibition and the extent to which inhibition was due to toxicity. The crude extract and partially purified fractions of A.elongata showed significant inhibition over the settlement individually, and with the interaction of bacterial species. No bacterial film stimulated the barnacle settlement. The high but variable levels of antifouling activity in combination with less amount of toxicity showed the potential of these metabolites in environmentally-friendly antifouling preparations.